Legal Protection of Copyright and Related Rights in Ukraine in the Context of International Law - Yurynets, Yu.L.; Belkin, M.L.; Belkin, L.M. (Science and Innovation, 2024)
Introduction. The development of the intellectual property law has been focused primarily on strengthening the protection of these rights. However, such enhanced protection leads to restrictions on the use of intellectual property. Therefore, it is necessary to find a proper balance. Problem Statement. The issues of legal protection of copyright and related rights shall be considered by the national legislator taking into account the international regulations. At present, the world has created a ramified system of international acts in this area, including, in certain conflicting aspects that require comprehensive consideration and, at the same time, created opportunities for maneuvering between the different norms embodied in different acts. Therefore, certain aspects of the legal regulation of copyright and related rights under 9 key international acts (Berne Convention, Universal Copyright Convention, Treaty on the International Registration of Audiovisual Works, World Intellectual Property Organization (WIPO) — Treaty on Copyright Law and Performances and Phonograms, Rome Convention, Geneva Convention, Brussels Convention on the Distribution of Signals Carrying Programs Transmitted via Satellites, TRIPS Agreement) have been compared with each other and with the Ukrainian legislation in terms of optimization of legal regulation. Purpose. To generalize international legal regulation of copyright and related rights and to compare it with the Ukrainian legal regulation. Materials and Methods. The methods of documentary analysis and synthesis, comparative analysis, objective truth, etc. have been used. Results. The legislation of Ukraine absolutizes the protection of copyright and related rights. In the context of the international discourse on the liberalization of restrictions on the use of intellectual property, the Ukrainian legal regulation does not fully comply with the modern international trends. Conclusions. The absolutization of the protection of copyright and related rights does not automatically makes such protection consistent with the international standards. Recently, the world has developed an understanding of the need to harmonize the interests of authors (performers) with the interests of the society for access to the objects of these rights.